Integrated 16s RNA sequencing and network pharmacology to explore the effects of polyphenol-rich raspberry leaf extract on weight control - Wang, Tao; Yang, Jing; Huang, Ziang; Wang, Fei; Liu, Ruzi; Liu, Yongping; Li, Xiaojun (Frontiers in Nutrition, 2024)
Obesity is recognized as a chronic low-grade inflammation associated with intestinal flora imbalance, leading to dyslipidemia and inflammation. Modern research has found that polyphenols have anti-obesity effects. However, the mechanism of action of raspberry leaf extract (RLE) with high polyphenols in regulating obesity is still unknown. This study investigated the improvement of obesity in mice induced by high fat diet (HFD) through RLE supplementation during the prevention and treatment stages. The results showed that RLE effectively prevented and treated weight gain in obese mice induced by HFD, alleviated adipocyte hypertrophy, reduced Interleukin-6 and Tumor Necrosis Factor Alpha levels, and improved intestinal flora, especially Muriaculaceae, Alistipes and Alloprevotella, and decreased the Firmicutes/Bacteroidota ratio. Network pharmacology analysis selected 60 common targets for 7 RLE polyphenols (quercetin-3-O-glucuronide, ellagic acid, kaempferol-3-O-rutinoside, chlorogenic acid, brevifolin carboxylic acid, quercetin-3-O-rutinoside, and quercetin) and obesity. Combined with protein-protein interaction network, enrichment analysis and experimental results, TNF, IL-6, AKT1, and PPAR, were predicted as potential key targets for RLE polyphenols.